2012
DOI: 10.5056/jnm.2012.18.2.174
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic and Diagnostic Value of 2-week High Dose Proton Pump Inhibitor Treatment in Overlapping Non-erosive Gastroesophageal Reflux Disease and Functional Dyspepsia Patients

Abstract: Background/AimsTo evaluate the value of a 2-week high dose proton pump inhibitor (PPI) treatment on patients with overlapping non-erosive gastroesophageal reflux disease (NERD) and functional dyspepsia (FD).MethodsSixty overlapping NERD and FD patients with symptom onset > 3 months prior underwent 24-hour esophageal pH monitoring studies. All patients received rabeprazole 20 mg b.i.d. for 2 weeks. The reflux and dyspeptic symptoms were evaluated using a symptom questionnaire with 4-point Likert scales before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Each symptom was scored 0–3 according to its influence on patients' daily activities: 0, absent; 1, mild (symptoms presented but not interfere with daily activities); 2, moderate (symptoms presented and interfere with but not preclude daily activities); 3, severe (symptoms interfere with daily activities markedly enough to urge modification) . This questionnaire has been validated and used in our previous study . The patients who had heartburn and/or acid regurgitation as their main problem were classified as typical reflux symptom, and the patients who had upper abdominal pain or discomfort as their main problem, accompanying with any severity of heartburn and/or acid regurgitation, were classified as reflux‐like dyspepsia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each symptom was scored 0–3 according to its influence on patients' daily activities: 0, absent; 1, mild (symptoms presented but not interfere with daily activities); 2, moderate (symptoms presented and interfere with but not preclude daily activities); 3, severe (symptoms interfere with daily activities markedly enough to urge modification) . This questionnaire has been validated and used in our previous study . The patients who had heartburn and/or acid regurgitation as their main problem were classified as typical reflux symptom, and the patients who had upper abdominal pain or discomfort as their main problem, accompanying with any severity of heartburn and/or acid regurgitation, were classified as reflux‐like dyspepsia.…”
Section: Methodsmentioning
confidence: 99%
“…17 This questionnaire has been validated and used in our previous study. 8 The patients who had heartburn and/or acid regurgitation as their main problem were classified as typical reflux symptom, and the patients who had upper abdominal pain or discomfort as their main problem, accompanying with any severity of heartburn and/or acid regurgitation, were classified as reflux-like dyspepsia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It has been shown that SGB can exacerbate GERD symptoms by directly inducing reflux episodes. 3,5,6 PPIs are used widely in GERD treatment and have been used for belching, [8][9][10][11] but do not directly address the pathophysiology of SGB.…”
mentioning
confidence: 99%
“…Proton-pump inhibitors (PPIs) which are commonly used in treatment of GERD symptoms are considered effective in reducing the number of belches as well [19][20][21][22]. Perhaps this can be explained by the notion that PPIs reduce the unpleasant abdominal or retrosternal sensation that triggers the behavior and leads to supragastric belching.…”
Section: Belching In Patients With Gastroesophageal Reflux Disease (Gmentioning
confidence: 99%